Regression dependence of the efficacy of pre-emergence herbicides in common ragweed control on the dose and number of days after herbicide application - Mitrić, Siniša; Golić, Darko; Janjić, Vaskrsija; Božić, Dragana; Kovačević, Zlatan; Jovanović, Vladan; Biljana Kelečević, (Acta herbologica, 2022)
The aim of the research is to determine the efficacy of 12 pre-emergence herbicides in control of common ragweed (Ambrosia artemisiifolia L.), and these are: atrazine, alachlor, acetochlor, alachlor + linuron, S-metolachlor, pendimethalin, metribuzin, prometryn, napropamide, imazethapyr, oxyfluorfen and dichlobenil. The research lasted for two years and herbicides were applied in May on the soil that had been prepared for sowing but not sown. The efficacy was observed 30, 45 and 60 days after the application. Herbicides were used in 4 different doses: D1 which is ½ of the recommended dose, D2 is the lowest recommended dose, D3 is the highest recommended dose and D4 is the dose where the herbicides were used with the dose higher than it is recommended (D3×1,5). Efficacy is expressed as the percentage of efficacy for the number and fresh mass of weeds in relation to the control. Coefficient of multiple correlation between the percentage of efficacy (PE), as a dependent variable, and the dose (D) and the number of days from the application of herbicides (DAA), as independently variable, is statistically significant and in all cases it ranges from 0,853** to 0,961****. Partial coefficient correlation of dependence percentage of efficacy, on the herbicide dose is positive and in almost all cases significantly high, varied from 0,739** to 0,956****. The partial correlation coefficient between the percentage of herbicide efficacy for common ragweed mass and days after herbicide application is negative and statistically significant or highly significant and varies from -0,606* to -0,904***. The partial correlation coefficient between the percentage of herbicide efficiency for the number of common ragweed plants and days after herbicide application, is also negative and varies, depending on the herbicide, from -0,182NZ to -0,923****.
Keywords: common ragweed, herbicides, dose, days after herbicide application